Perilaku Konsumtif Followers Akun @discountfess Pada Media Sosial X - Rahma Mudhiyanti; Dian Alfia Purwandari; Sujarwo Sujarwo (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Globalization brings many influences and changes in human life. The rapid dissemination of information obtained through social media can cause change. X account @discountfess as a forum that favolitates the dissemination of information quickly and widely can influence a person's behavior, one of wich is consumprive behavior. This study aims to describe the consumptive behavior of folllwers account @discountfess at social media X, using a descriptive method of quantitative approach. Sampling was accidental sampling with 96 followers @discountfess account. Data collection techniques include observation, questionnaire, documentation and literature study. The results show that the consumptive behavior of followers account @discountfess that causes impulsive purchases in the moderate category of 57%, irrational purchase in the moderate category with a percentage 60% and waste in the high category with a percentage 52%.